A referência anafórica por encapsulamento: gramática e discurso - Pacheco, Lucivânia Marques [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The goal of this work is to analyze the functioning of anaphoric encapsulation, taking into account the instances in which this phenomenon takes place. Based on the postulates of Functional Discourse Grammar of Hengeveld and Mackenzie (2008), this study aims to show that there is an instance of referencing that is marked in grammar and another component - the identification of the textual portion of an anaphoric encapsulation - that is solved in the Contextual Component, as postulated by Hengeveld and Mackenzie (Unpublished). By means of a dialogue with the works of Connlly (2007), Cornish (2009) and Stassi-Sé (2012), this study highlights the need for a redefinition of the Contextual Component. This proposal is confirmed by the analysis of reference encapsulation occurrences found in personal opinion texts circulating in two weekly magazines (Veja and Caros Amigos Online). The analysis of those events suggests that the phenomenon of anaphoric referencing through encapsulation articulates properties of socio-cognitive, discursive, semantic and morphosyntactic nature and that some regularities of its functioning are explained through the levels and layers of the FDG

O objetivo deste trabalho é analisar o funcionamento do encapsulamento anafórico, levando em consideração as instâncias em que esse fenômeno se processa. Com base nos postulados da Gramática Discursivo Funcional, de Hengeveld e Mackenzie (2008), este trabalho pretende mostrar que há uma instância da referenciação que se marca no Componente Gramatical e outra – a da identificação da porção textual de um encapsulamento anafórico – que se resolve no Componente Contextual, postulado conforme Hengeveld e Mackenzie (Inédito). Dialogando com dos trabalhos de Connlly (2007), Cornish (2009) e Stassi-Sé (2012), esse trabalho aponta a necessidade de uma redefinição do Componente Contextual. Essa proposta se confirma por meio da análise de ocorrências de referência por encapsulamento encontradas em textos do gênero artigo de opinião que circulam em duas revistas semanais (Veja e Caros Amigos Online). A análise dessas ocorrências aponta que o fenômeno da referenciação anafórica por encapsulamento articula propriedades de natureza sociocognitiva, discursiva, semântica e morfossintática e que algumas regularidades do seu funcionamento encontram explicação por meio dos níveis e camadas da GDF
Keywords: Linguística; Análise linguística; Funcionalismo (Linguística); Anafora (Linguistica); Referencia (Linguistica); Linguistic analysis (Linguistics)